Simulacija bočnega nihanja potniških vagonov - Bazaras, Žilvinas (Strojniški vestnik, 2005)
In this investigation we look at the dynamics of railway passenger wagons, themethods of providing solutions and the dynamic processes of a carriage. Using the program package ADAMS/Rail, a mathematical model is created to calculate the transversally forced oscillations of the carriage. During the creation of this model the geometrical and mechanical characteristics of the carriage are estimated. In addition, the functions describing the sinusoidal irregularities of the road in the plane are presented for cases when the sinusoidal wavelength is 10 m, 20 m, 30 m and 40 m, and the wave amplitude is 0.0025 m, 0.0035 m, 0.0050 m and 0.0065 m. With the help of these functions the excitation influence on the dynamic system is described.
Keywords: vagoni potniški; dinamika; nihanja bočna; modeli matematični; vagoni; nihanje; matematični modeli